Atributos químicos, físicos e mineralógicos de latossolos afetados pelo aquecimento - Costa, Yasmmin Tadeu (2018)
The heating effects on chemical and mineralogical properties of soils from temperate climate, young and organic-rich are well known, however, scarce information can be found for highly weathered-leached soils of tropical regions. In this context, it is important to highlight the significant occurrence of natural or induced fire in Brazil. We aimed to evaluate the burning effects on chemical, physical and mineralogical properties of six contrasting Oxisols under laboratory conditions. Surface samples (0-5 cm), sieved (<2 mm), aggregates size (12-19 mm and 4-8 mm) and clay fraction were used. Using a muffle furnace the soil samples were submitted to the following temperatures (ºC) during 30 minutes: 100, 200, 300, 400, 500 and 600. After each thermal treatment the soil samples were analyzed for: soil organic matter, net surface charge, soil reaction, nutrients availability and qualitative mineralogical alteration. It was also evaluated the soil color change using a portable sensor, the soil aggregate stability by the wet sieving method, water repellency and tensile strength tests.The studied Oxisols had the same behavior regarding the effects of heating on chemical and mineralogical properties. The relationship between exposed temperature and changing of soil properties is not directly proportional; it is depends on soil organic matter and mineralogical transformations. In general, temperatures up to 300º C promoted increase of nutrients availability and reduced 50% of soil organic matter; highest temperatures (above 300º C) led to decrease of nutrients availability and total organic matter depletion. After heating the net charges of soils were closed to zero. Changes in soil color reflect the observed chemical and mineralogical alterations. The water repellency and tensile strength of the Oxisols were significantly influenced by the heating. As the organic matter reduced the water repellency and tensile strength reduced. However, the aggregates 4-8 mm increased the resistance to disruption in water. The interpretation of soil structure assessment should be strongly considered. The dry aggregates of the Oxisols affected by the heating became more susceptible todisruption due to compression, however, became more resistant to detachment in water.